Confined ammonia borane nanocarriers: Tubular and fibrous structures based solid-state hydrogen storage composites - Aydin, Doga Su; Filiz, Bilge Coskuner; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
This paper introduces a confinement approach to enhance solid -state hydrogen storage by designing a nanotubular and nano-fibrous structured boron-based storage medium. We detail the preparation of the confinement matrix, emphasizing its nanotubular and microfibrous structures provided by activated halloysite and sepiolite clays to achieve suitable confinement for ammonia borane (NH 3 BH 3 , AB). The thermolysis characteristics are thoroughly investigated in a lab-scale hydrogen reactor, elucidating the activation effects (thermal, acid, and both thermal-acid) on confinement and hydrogen generation performance. The resulting composite exhibits improved thermal stability and controlled hydrogen desorption characteristics, offering great promise for safe and efficient hydrogen storage applications. This research underscores the potential of tailored nanomaterials in advancing hydrogen storage technologies, with significant implications for clean energy solutions and the sustainable transportation sector. AB confined in acid-activated nano-tubular clay has shown improved hydrogen generation features at 120 degrees C, resulting in the highest improvement in H 2 equivalent per AB mole (98 %) and the initial hydrogen generation rate (233 %) while minimizing induction time up to 90 %.
Keywords: Ammonia borane; Confinement; Hydrogen; Storage; Clay activation; METAL-ORGANIC FRAMEWORK; THERMAL-DECOMPOSITION; H-2 RELEASE; HYDROLYSIS; THERMOLYSIS; DEHYDROGENATION; TEMPERATURE; ADSORPTION; GENERATION; CATALYSTS; Chemistry; Electrochemistry; Energy & Fuels